Framework for a sustainable smart retirement city: a local perspective / Mohd Zool Hilmie Mohamed Sawal ... [et al.] - Mohamed Sawal, Mohd Zool Hilmie; Noordin, Nazmi@Nazni; Zakaria, Zaherawati; Azmi, Muhammad Syahmizan; Aminuddin, Adnan; Shafie, Zakba (Universiti Teknologi MARA, Kedah, 2023)
The world's population aged 60 and older is projected to increase to 4 billion by 2050. By 2030, 15.3 percent of Malaysia's population will be over 60, a number that is expected to rise. To enhance the lives of the elderly, the government should construct a retirement city framework. Through in-depth interviews with retirees and theme analysis, this research presents a sustainable smart retirement city framework that takes into account five key areas: smart living, smart people, smart infrastructure, smart economy, and smart environment.